Appropriation of Public Urban Space as an Effect of Privatisation and Globalisation - Mierzejewska, Lidia (Quaestiones Geographicae, 2011)
The changes taking place in the public space of many cities of the world have been assessed as harmful. They are seen as resulting from modern processes shaping their spatial-functional structure. Among them are advancing privatisation, which leads to various forms of public space appropriation, and globalisation, which transforms the world from a world of cities and places into one of networks (especially the Internet and motorways). In Polish cities, however, the deterioration in the quality and accessibility of public spaces is due not only to the social awareness developing in the conditions of neoliberalism and a market economy, which puts private property above public to get over the experience of feasible socialism, but to some extent also to Polish legislation. The aim of this article is to present forms and ways of appropriation of public urban space in the conditions of privatisation and globalisation, as well as reasons why this development seems to intensify in the Polish conditions.